(untitled) (Journal of Psychiatrists’ Association of Nepal, 2023)
Background: Olfactory Dysfunction (OD) post-SARS-CoV-2 infection can manifest in various forms, including qualitative impairments such as parosmia. We describe a 26-year-old woman’s trajectory from anosmia following COVID-19 infection to parosmia, which evolved into severe depression. This young woman from North India began perceiving a "garbage-like" odor from food items several months after recovering from COVID-19. Her distress from this condition, exacerbated by her family’s lack of understanding, led to significant dietary restrictions, weight loss, and subsequent development of an episode of severe depression linked to the distress from her persistent olfactory dysfunction. A combination of escitalopram, olanzapine, and carbamazepine was initiated alongside psychoeducation sessions for the family. Over the following months, her depressive and olfactory symptoms showed significant improvement. This case illuminates the complex relationship between sensory dysfunction and mental health post-COVID-19, emphasizing the need for an integrated biopsychosocial treatment approach and the crucial role of familial understanding and support.